Influence of Identity Development on Weight Gain in Adolescent Anorexia Nervosa - Budde, Lynn I.; Wilms, Simon; Föcker, Manuel; Dalhoff, Anke; Müller, Joerg M.; Wessing, Ida (Frontiers in Psychiatry, 2022)
Background: Anorexia Nervosa (AN) typically begins during early adolescence, an important phase of personality development. A substantial proportion of adolescent AN patients shows impaired personality functioning, which might be a relevant but understudied aspect of illness severity. The developmental status of identity as key element of personality is suggested to influence inpatient treatment outcome in adolescents with AN. Methods: This study analyzed existing data of N = 60 adolescents with AN. Multilevel models assessed the influence of identity functioning, measured by the Assessment of Identity Development in Adolescence (AIDA) at admission, on weight gain (BMI (body mass index), BMI-SDS (BMI standard deviation score)) during ten weeks of inpatient treatment. Moreover, the influence of other indicators of illness severity, i.e. eating disorders and comorbid psychopathologies, was explored. Results: As expected, higher AIDA scores negatively influenced the course of weight gain. A similar effect was observed for other psychopathology measures, especially body image distortion. In general, higher weight at admission was associated with less weight gain. Higher weight at admission was also predicted by higher other psychopathology measures, but not AIDA scores. Conclusion: The course of weight gain during inpatient treatment was hampered in adolescent AN patients who have difficulties developing a stable identity. Unlike other aspects of psychopathology, this was independent of the initial weight. Thus, in addition to the level of underweight and other aspects of psychopathology, difficulties in identity development constitute a relevant aspect of illness severity in AN. This recommends consideration of identity development during treatment.